2006
DOI: 10.2514/1.15127
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Nonlinear Frequency Domain Methods

Abstract: This paper demonstrates the accuracy of the nonlinear frequency domain method in applications to unsteady flow calculations. The basis of the method is a pseudospectral approach to recast a nonlinear unsteady system of equations in the temporal domain into a stationary system in the frequency domain. The nonlinear frequency domain method, in principle, provides the rapid convergence of a spectral method with increasing numbers of modes, and, in this sense, it is an optimal scheme for time-periodic problems. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 11 publications
0
60
0
Order By: Relevance
“…!N , such that u = with jk = k (t j ) = e i!ktj (4) serving as the transformation operator. The di↵erentiation operator is applied in the frequency domain, i.e.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…!N , such that u = with jk = k (t j ) = e i!ktj (4) serving as the transformation operator. The di↵erentiation operator is applied in the frequency domain, i.e.…”
Section: mentioning
confidence: 99%
“…Expanding the temporal variation at each spatial node into a Fourier series transforms the unsteady governing equations into a coupled set of steady equations in integer harmonics that can be tackled with the acceleration techniques a↵orded to steady-state flow solvers. Other similar approaches, such as the Nonlinear Frequency Domain [3,4,5], Reduced Frequency [6], and Time-Spectral [7,8,9] methods, were developed shortly thereafter. Additionally, adjoint-based optimization techniques [10,11] can be applied to provide the ability to perform design optimization without resorting to costly unsteady adjoint methods.…”
Section: Introductionmentioning
confidence: 99%
“…Helicopter flows in forward flight, turbomachinery blades and wind turbine are constantly subjected to unsteady loads. For this class of problems, Gopinath & Jameson 24 have shown that the Time Spectral method is superior in terms of the accuracy and computational efficiency to the typical implicit dual time stepping scheme or the hybrid scheme proposed by Hsu & Jameson. 25 The Time Spectral method takes advantage of the periodic nature of the flow and is simpler than the typical nonlinear frequency domain type solver proposed by Hall et al 26 and McMullen et al [27][28][29] as it does not require the operations of Fourier transforms and inverse Fourier transforms.…”
Section: Introductionmentioning
confidence: 99%
“…In an extension of this work, Ekici and Hall [43] applied the technique, known as the harmonic balance technique, to multistage turbomachinery applications where a variety of frequencies may be present. Other spectral methods have been demonstrated by McMullen et al [44,45] (the nonlinear frequency domain (NLFD) method) and Gopinath and Jameson [46] (the time-spectral method). The main differences between the methods are the portions of the solution that are computed in the frequency and time domains.…”
Section: A Time-spectral Cfdmentioning
confidence: 99%